A numerical study of effect of cold temperature on growth orientation of horizontal fractures using displacement discontinuity method. (September 2022) - Shi, Jingyu; Shen, Baotang
Abstract: We study the effect of temperature change in the fracture on the orientation of fracture propagation in the hydraulic fracturing process. Hydraulic fracturing technologies have been employed in many industries to increase operation products or reduce operation risks. In the hydraulic fracturing process with double fractures, the fractures propagate away from the original orientation under the influence of fluid pressure. It was found recently that cold fluid temperature in the fractures causes the fractures to propagate in the opposite direction from that caused by fluid pressure. Therefore, it seems that cold temperature of the fluid in the fractures could reduce the curvature of the fractures. In this study, we use FRACOD 3D code, which employs combined displacement discontinuity method for fracture propagation and an indirect boundary element method for thermal conduction in rocks, to simulate propagation of fractures in three-dimension under fluid pressure and thermal conditions. Particularly we focus on the effect of cold temperature of the fluid on the growth orientation of fractures in hydraulic fracturing. Highlights: A combined indirect method with boundary elements outlined. Propagation of two nearby fractures under temperature change studied. Effect of cold fluid on hydraulic fracturing configurations investigated.